Pengaruh Pembelajaran Berbasis Aplikasi Telegram Terhadap Minat Belajar Peserta Didik Pada Materi Sejarah Pendidikan Islam di SMAN 1 Cikampek Karawang - Aprilia Saputri, Angelina (HAWARI : Jurnal Pendidikan Agama dan Keagamaan Islam, 2025)
This research consists of two variables, namely telegram application-based learning and students' learning interest, so the aim of this research is to describe the picture of telegram application-based learning outcomes, students' learning interest, and the influence of the two in a correlational relationship. The population in this study were all students of SMAN 1 CIKAMPEK, and the sample was class XI students. The research method used in this research is correlational research with a quantitative approach. This method was chosen to identify the relationship between telegram application-based learning and students' learning interest. Data related to telegram application-based learning experiences and students' learning interests were collected using a questionnaire instrument, which was prepared using a Likert scale, data analysis techniques used descriptive and inferential analysis. The results of this research show that 43% of students' Telegram Application Based Learning is in the low category, 52% is in the medium category, 5% is in the high category, so it can be concluded that the average Telegram Application Based Learning of SMAN 1 CIKAMPEK students is in the medium category. 63% of students' learning interest is in the low category, 5% is in the medium category, 32% is in the high category, so it can be concluded that the average learning interest of SMAN 1 CIKAMPEK students is in the low category. Based on the SPSS output in the Coefficientsa table, it is known that the significance value (sig) is 0.000 <0.05 so it can be concluded that H0 is rejected and Ha is accepted, which means that "There is an influence of telegram application-based learning (X) on students' learning interest (Y). From the results of the analysis, it is known that the R Square value = 0.317, thus it can be concluded that the influence of learning based on the Telegram application (X) on students' learning interest (Y) is 31.7%, while 63.1% of learning interest is influenced by other variables that are not become a variable of this research